2022
DOI: 10.3390/ijerph19159140
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Assessment, and Source of Heavy Metals in Sediments of the Qinjiang River, China

Abstract: Heavy metals are toxic, persistent, and non-degradable. After sedimentation and adsorption, they accumulate in water sediments. The aim of this study was to assess the extent of heavy metal pollution of Qinjiang River sediments and its effects on the ecological environment and apportioning sources. The mean total concentrations of Mn, Zn, Cr, Cu, and Pb are 3.14, 2.33, 1.39, 5.79, and 1.33 times higher than the background values, respectively. Co, Ni, and Cd concentrations are lower than the background values.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…The results indicated almost all the sampling stations were of a fine (silt clay) and sand type. These findings signify that sediment grains with fine sizes (silt clay) probably influence heavy metal accumulations in the sediments [83].…”
Section: Characterization Of Sediment Texturementioning
confidence: 66%
See 1 more Smart Citation
“…The results indicated almost all the sampling stations were of a fine (silt clay) and sand type. These findings signify that sediment grains with fine sizes (silt clay) probably influence heavy metal accumulations in the sediments [83].…”
Section: Characterization Of Sediment Texturementioning
confidence: 66%
“…Owen, [82], reported that fine-grained sediment like silt clay is responsible for a significant proportion of the annual transport of metals. Various sources in the literature revealed that silt clay (fine-particle) has a high uptake of heavy metals due to the fact it has a large surface area [83,84]. A similar study performed by Vaithiyanathan et al [85] reported that metal absorption rates are various at different grain sizes.…”
Section: Characterization Of Sediment Texturementioning
confidence: 95%
“…The geological accumulation index ( I geo ), commonly referred to as the Muller index [ 35 ], is a parameter that distinguishes the impact of anthropogenic activities and is calculated by the following Equation (2): where C i is the measured content of heavy metal i ; k is the correction index ( k = 1.5); B i is the soil background value of heavy metal i . According to the ground accumulation index I geo , the pollution level is divided into 7 levels [ 36 , 37 ], among which, 0~6 levels are: I geo < 0, no pollution; 0 ≤ I geo < 1, no pollution to moderate pollution; 1 ≤ I geo < 2, moderate pollution; 2 ≤ I geo < 3, moderate pollution to strong pollution; 3 ≤ I geo < 4, strong pollution; 4 ≤ I geo < 5, strong pollution to very strong pollution; I geo ≥ 5, very strong pollution.…”
Section: Methodsmentioning
confidence: 99%
“…Cadmium levels in each site at northern coast of Central Java of cadmium was 0.027+ 0.021 mg.kg -1 . The heavy metal contamination in the water in vannamei shrimp ponds, it has been found that the health of organisms is negatively affected, especially those involved in vannamei shrimp aquaculture (Zhang et al, 2022). Because of heavy metal contamination, the plankton that is naturally available for vannamei shrimp to feed upon is adversely affected.…”
Section: Heavy Metal Contaminants In Vannamei Shrimp Sediment and Watermentioning
confidence: 99%